STRATEGI INVESTASI SAHAM PERBANKAN SYARIAH DI INDONESIA DENGAN MENGGUNAKAN METODE DOLLAR-COST AVERAGING UNTUK TERCAPAINYA EFEKTIVITAS INVESTASI JANGKA PANJANG - Abdillah Mundir; M. Ryan Hidayat; M. Ridwan Alviansyah; A. Rafi Maulana (Jurnal Ekonomi Syariah Darussalam, 2024)
This article discusses the investment strategy of Islamic bank stocks in Indonesia using dollar-cost averaging as a method to achieve long-term investment efficiency, by identifying Islamic banking principles that affect investment in Islamic bank stocks and analyzing how dollar-cost averaging can be effectively applied in this context. The dollar-cost averaging approach is designed to consider its potential benefits in reducing the risk of market volatility and increasing asset accumulation over a longer period of time. As technology develops and the financial industry develops in Indonesia, investing has become easier for everyone. For novice investors, understanding and analyzing stock selection can be increasingly difficult. Therefore, considering the risk, amount of money spent, and time value of money, choosing the dollar-cost averaging method is the most suitable strategy for beginner investors. It minimizes the losses incurred while investing.